THE USAGE OF TOTAL PHYSICAL RESPONSE IN PRIMARY SCHOOLS IN UZBEKISTAN - Akbarova , Dilzodaxon (QO‘QON UNIVERSITETI XABARNOMASI, 2025)
In this article authors study the usage of the Total Physical Response (TPR) approach in Uzbekistan primary schools with an emphasis on first-grade classes. Because it integrates spoken language with physical activities, TPR is seen to be one of the best methods for teaching second languages because it helps students make the connection between language and movement. For young students in particular, this method is advantageous since it makes the learning process more dynamic, interesting, and memorable. Through the use of physical responses, children are able to internalize vocabulary more effectively and demonstrate better comprehension of new concepts. The study emphasizes that the integration of TPR not only motivates learners but also creates a supportive classroom atmosphere. Consequently, developing and implementing TPR in primary education can lead to significantly improved learning outcomes.